Evaluating the effects of climate change on the water resources for the city of Birmingham, UK - Warren, Andew J.; Holman, Ian P. (Blackwell Publishing Ltd., 2012)
Climate change is expected to affect precipitation patterns and may therefore impact upon water resource availability. The city of Birmingham in central England receives its public water supply from a catchment in the Elan valley, mid Wales. Baseline and future climate projections generated from a stochastic weather generator within the United Kingdom Climate Projections 2009 and a daily soil water balance model (WaSim) were used to determine the potential impacts of climate change on Hydrologically Effective Rainfall (HER). Annual HER is likely to decrease from baseline conditions (> 90% likelihood that HER will be reduced), with more frequent and persistent very dry spells and increasing seasonality. It is concluded that climate change will put additional stress on water resources for the city of Birmingham so that, coupled with expected increases in demand, adaptation measures to increase supply and / or reduce demand are likely to be needed.